INTERACTION DESIGN OF VIRTUAL TRY-ON FOR FASHION PRODUCT CATEGORY ON E-COMMERCE - Mutiara Windyarahma, Jingga
The rapid development of technology has caused a shift on human behavior when it comes to shopping, including buying basic necessities such as clothes, which have become easily purchased through e-commerce. Even if online shopping has its own perks such as ease and practicality, it has some consequences such as the possibility of disappointment when the clothing product doesn’t meet customer’s expectations once arrived. However, current existing features on e-commerce have not provided a personalized virtual experience where users can match clothing products with their own characteristics. Hence, this research aims to produce an interaction design of a virtual try-on feature for fashion product category which can help users to make better decision when buying clothes. This research adopts the user-centered design (UCD) methodology by ISO 9241-210 which directly involves target users in its processes and consists of four main steps: identifying context of use, specifying the requirements,